2020
DOI: 10.1002/eat.23222
|View full text |Cite
|
Sign up to set email alerts
|

Teammate influences, psychological well‐being, and athletes’ eating and exercise psychopathology: A moderated mediation analysis

Abstract: Objective: Positive and negative influences from teammates (e.g., supportive teammate friendships, modelling of teammates' disordered eating) have been associated with athletes' eating/exercise psychopathology. However, research is yet to explore how an athlete's psychological well-being and gender may impact upon these relationships. This study aimed to explore whether psychological well-being mediates the relationship between teammate influences and eating/exercise psychopathology, and to determine whether g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Most of the literature on body image, it is focused on testing how physical activity and sport are associated with more positive body image, or how sports and physical activity interventions can be used to improve body image 17 . When we look at the literature, there are many studies that deal with social appearance anxiety 26,27,28,29,8,30 and psychological well-being 31,32,33,34,35,36,37,38,39 with different variables in the context of sports. However, no study has been found in which the relationship between social appearance anxiety and psychological well-being is discussed together in the context of pilates.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature on body image, it is focused on testing how physical activity and sport are associated with more positive body image, or how sports and physical activity interventions can be used to improve body image 17 . When we look at the literature, there are many studies that deal with social appearance anxiety 26,27,28,29,8,30 and psychological well-being 31,32,33,34,35,36,37,38,39 with different variables in the context of sports. However, no study has been found in which the relationship between social appearance anxiety and psychological well-being is discussed together in the context of pilates.…”
Section: Introductionmentioning
confidence: 99%
“…Females are also more likely than males to have both larger and more supportive social support networks (Eshbaugh, 2008; Kahn & Antonucci, 1980). Both male and female athletes benefit from having supportive teammate relationships (Scott et al, 2020). A recent study indicated that males reported smaller social support networks and less quality in their social support (Kneavel, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other findings also seem to partially support the expected relationships. Scott et al, (2020Scott et al, ( , 2021 found with athletes from lean and non-lean sports that relationships with teammates and team connectedness were associated with reduced disordered exercise behavior and that teammate negative influences on eating and exercise psychopathology were mediated by athletes' psychological distress. Perfectionistic strivings have been found to predict engaging in compulsive exercise for mood improvement, whereas perfectionistic concerns have been found to predict compulsive exercise for both avoiding negative affect and weight control among athletes from several sports (Madigan et al, 2017).…”
Section: Understanding Ea In the Sports Context: From Theory-guided Research To Empirically Based Practicementioning
confidence: 99%